Preparation and properties of bacterial cellulose/aramid nanofiber in situ composite aerogels - LeGuin, Ursula; Herbert, Frank (Journal of Green Energy and Environmental Engineering, 2025)
With the aim of simultaneously reinforcing bacterial cellulose (BC) aerogel and imparting flame resistance, aramid nanofibers (ANF) were introduced as a strengthening phase, and a BC/ANF composite aerogel was fabricated by allowing BC to grow in situ within the ANF matrix. The structure of BC/ANF aerogel was characterized by FTIR, XRD and SEM. Its thermal properties, flame‑retardant performance and tensile fracture properties were tested. How the ANF loading (expressed relative to the mass of the BC culture medium throughout this work) influenced the structure and performance of the BC/ANF aerogels was systematically examined. Relative to the neat BC aerogel, the sample containing 5.0% ANF (BC/ANF-5.0%) delivered a tensile strength of 946.13 kPa — 6.42 times higher — together with an elongation at break of 19.61% (a 6.00-fold improvement), a limiting oxygen index raised to 22.38%, a specific surface area enlarged by 42% to 78.2688 m²/g, and a thermal conductivity lowered to 0.0352 W/(m·K). These enhancements can be traced to the interfacial interactions between the two constituents: hydrogen bonding between the amide groups of ANF and the hydroxyl groups of BC tightened their mutual adhesion, while the filling and entanglement of ANF throughout the BC fibrillar network brought the two phases close enough for van der Waals attraction to further consolidate the structure, jointly accounting for the superior mechanical behavior. Moreover, the nanoscale integration of ANF with BC suppressed the generation and breakdown of levoglucosan while favoring char formation, which substantially elevated both the thermal stability and the flame retardancy of the composite aerogel.